PERILAKU MASYARAKAT DALAM PENGELOLAAN SAMPAH ANORGANIK DI KECAMATAN ABEPURA KOTA JAYAPURA PROVINSI PAPUA - , ALBERTH. E.S. ABRAUW, S.T; , Prof.Dr. Hadi Sabari Yunus, M.A, DRS. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was conducted in AbepuraSubdistrict, Jayapura City, Papua Province. The inorganic waste management in this area is explored through studying peopleâs behavior. The research objectives are to: 1) study the social-economic characteristics of the community in the research area